2013
DOI: 10.1159/000354454
|View full text |Cite
|
Sign up to set email alerts
|

EGF Activates Autocrine TGFα to Induce Prolonged EGF Receptor Signaling and Hepatocyte Proliferation

Abstract: Background/Aims: EGF receptor is a main participant in the regulation of liver regeneration. In primary hepatocyte cultures, EGF or TGFα binding to EGF receptor activates Erk1/2 and PI3K pathways, induces cyclin D1 and thus initiates DNA synthesis. We have explored mechanisms by which prolonged EGF receptor activation induces hepatocyte proliferation. Methods: EGF receptor activation, as well as Erk1/2 and PI3K signaling were explored in EGF-stimulated primary hepatocyte cultures by Western blotting and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…It has been reported that specific TFs, such as, C/EBP, AP-1, STAT3, EGF and NF-κB are rapidly activated in the remnant liver tissues shortly after PH [10,11,[18][19][20][21][22][23]. These events were followed by the first phase of gene expression alteration, including the upregulation of a group of promitogenic proto-oncogenes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that specific TFs, such as, C/EBP, AP-1, STAT3, EGF and NF-κB are rapidly activated in the remnant liver tissues shortly after PH [10,11,[18][19][20][21][22][23]. These events were followed by the first phase of gene expression alteration, including the upregulation of a group of promitogenic proto-oncogenes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Activating Gp1 mGluRs leads to elevated Phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) or Extracellular Signal-regulated Kinase-1/2 (ERK1/2) signaling (14)(15)(16), which in turn activates eIF4E and translation initiation (17)(18)(19)(20)(21). Several recent studies have also demonstrated that translation elongation is facilitated upon mGluR activation through the phosphorylation of eukaryotic elongation factor 2 (eEF2) (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…18 Park7 has been shown to facilitate liver progenitor cell expansion in a 3,5diethoxycarbonyl-1,4-dihydrocollidine diet-induced liver injury murine model 19 and promote the development of diethylnitrosamine-induced hepatocellular carcinoma 20 ; Park7 deficiency could improve carbon tetrachlorideinduced liver fibrosis and liver ischemia-reperfusion injury. 18,21 Several previous studies have shown that Park7 could activate several signalling pathways, such as ERK1/2 and PI3K/Akt, which are well documented to play a pro-proliferation role in liver regeneration 22,23 ; however, the role of Park7 in liver regeneration has not been investigated.…”
Section: Introductionmentioning
confidence: 99%